Spatiotemporal histogenesis of the developing human cerebellum reveals dynamic layering of Bergmann glia - Guanyi He; Simon Du; Henry Tan; Sri Yellampally; Anders W. Erickson; Virginia Fernandez; Ferechte Encha-Razavi; Kimberley A. Phillips; Christine Haberler; Nicole Amberg; Victor Borrell; Paul A. Northcott; et al. (Proceedings of the National Academy of Sciences, 2026)
Bergmann glia (BG) are a specialized glial population essential for cerebellar development, yet their developmental timeline and molecular identity in the human cerebellum remain poorly understood. Here, we combined detailed histopathological analysis with spatial transcriptomics and single-nucleus RNA sequencing to generate a developmental atlas of human cerebellar BG. Histology revealed that BG emerge around 11 postconception weeks (PCW), initially serving as a scaffold for Purkinje cells (PCs) migrating into the PC layer of the cerebellar cortex. Following the establishment of a multilayered PC arrangement, BG form a distinct parallel layer separated from the PCs by the lamina dissecans (LD), with both layers merging in the third trimester. This developmental sequence challenges earlier studies that suggested BG appear late in the third trimester. Comparative histology in mice, ferrets, and marmosets indicates that this trilaminar organization, including the LD, is likely unique to humans. Integration of spatial and single-nucleus transcriptomic datasets identified an ASCL1 + PTF1A + ventricular zone progenitor cluster giving rise to BG, astrocytes, and oligodendrocytes. Pseudotime analyses delineated three gliogenic lineages and revealed two temporally and transcriptionally distinct BG populations, emerging at 11–12PCW and 17PCW, suggesting multiphasic BG ontogeny. Together, these multimodal data link cellular lineage, spatial organization, and molecular identity of human cerebellar glia, providing a framework for future studies on the role of BG in cerebellar function and their potential contributions to vulnerability in neurodevelopmental disorders.